The role of flow cytometry in clinical diagnosis - Kaczmarek, Aldona; Mackiewicz, Andrzej; Leporowska, Ewa; Osawa, Tatsuya (Contemporary Oncology/Współczesna Onkologia, 2002)
Fluorescence Activated Cell Sorting (FACS) - flow cytometry is a modern instrument used to analyze the morphological features of cells, and it allows the evaluation of the degree of maturity and differentiation. The flow cytometry is now the perfered method used in the routine clinical diagnosis of hematological diseases. This method makes it possible to detect not only the phenotype of malignant cells, but also the source of its origin. Using commercially available monoclonal antibodies against the membrane and cytoplasmic proteins, a very precise diagnosis is possible in many cases. In the routine analysis, the panel for monoclonal antibodies is used to categorize the cellular linage of malignant cells and their phase of differentiation. This classification is based on the co expression of certain antigens and also the disappearance and appearance of others during the subsequent stages of normal cells development. If the process of differentiation and maturation are disturbed at an earlier phase, than the diagnosis based only on the morphology of cells becomes more difficult. The diagnostic value is also improved by using a wider panel including antibodies against proteins such as: apoptotic regulatory proteins (CD95, bcl-2, annexin, caspases) and the resistance for drugs (MDR), etc. The analysis of malignant phenotypes in leukemia and lymphoma plays a significant role in the diagnosis, detection of minimal residual diseases, controling of therapy, and also in deciding the course of treatment. The final diagnosis and classification of the disease is based on the correlation of immunological characteristics of abnormal cells, cell morphology, histology, and genetic analysis, and allows the deferenciation between hematologic, immunodeficient, and autoimmunologic diseases. The most important factors for the early diagnosis of these diseases are the percentage or the number of T lymphocytes (CD3) and its subpopulation CD4, CD8, as well as B lymphocytes (CD19, CD20) and natural killer (NK) cells (CD 16+56). The FACS improves the diagnostic value since it allows the analysis of larger number of cells, and the possibility to obtain more information about the cells. The flow cytometry allows the use of antibodies labeled with different fluorochromes and the analysis of co expression of antigens atypical for the line, which the tumor cells are derived from. Hematologic diseases are often non symptomatic, or the symptoms, if they occur, are in many cases unspecific. It is also very important to diagnose the disease at an early phase for the therapy to be successful. Therefore, control phenotype analysis should be performed in patients with immunological disorders. The substitution of manual method, with successful flow cytometric techniques, including FACS, makes it possible to analyze promptly and accurately, the rarely occurring and atypical subpopulation of cells. Moreover FACS is a complex, multiparameter technique which helps in the standardization of protocols in laboratory diagnostics.